Studi Struktur Komunitas Meiofauna dan Kualitas Perairan Zona Pesisir Losari Makassar - Muh. Sri Yusal (Jurnal Ilmu Alam dan Lingkungan, 2020)
The coastal zone of Losari Beach is located in a strategic position and rich in potential coastal resources, but the high density of human activities has decreased the quality of the surrounding waters. This study aimed to assesment of the meiofauna ecological index and important value index as a bioindicator of water quality in the coastal zone of Losari, Makassar. The study employed a quantitative descriptive approach with purposive sampling method. The measurement of interstitial meiofauna diversity value it is based on the Shannon-Wiener index from the ecological index results analysis (Diversity Index, Evenness Index, Dominance Index) which was first carried out the identification process using a binocular microscope and refers to the book Higgins & Thiel (1988); Giere (2009). The waters quality in the coastal zone of Losari Beach is categorized as heavily polluted (highly polluted), it is based on the interstitial meiofauna species diversity level which are lowest and mostly inhabited by meiofauna are be able to adapt to polluted aquatic environment. Ostracoda has a high influence on the structure of benthic organism community in the Losari coastal ecosystem, this type of meiofauna has high resources and ecological role in the bottom waters sedimentary environment, such as cleaning of seabed.